Routine Histopathologic Examination of Appendectomy Specimens: - Emre, A; Akbulut, S; Bozdag, Z; Yilmaz, M; Kanlioz, M; Emre, R; Sahin, N (2013)
The objective of this study was to analyze the clinical benefit of histopathologic analysis of appendectomy specimens from patients with an initial diagnosis of acute appendicitis. We retrospectively analyzed the demographic and histopathologic data of 1255 patients (712 males, 543 females; age range, 17-85 years) who underwent appendectomy to treat an initial diagnosis of acute appendicitis. Patients who underwent incidental appendectomy during other surgeries were excluded from the study. Histopathologic findings of the appendectomy specimens were used to confirm the initial diagnosis. Ninety-four percent of the appendectomy specimens were positive for appendicitis. Of those, 880 were phlegmonous appendicitis, 148 were gangrenous appendicitis with perforation, and the remaining 88 showed unusual histopathologic findings. In the 88 specimens with unusual pathology, fibrous obliteration was observed in 57 specimens, carcinoid tumor in 11, Encheliophis vermicularis parasite infection in 8, granulatomous inflammation in 6, appendiceal endometriosis in 2, and 1 specimen each showed mucocele, eosinophilic infiltration, Taenia saginata parasite infection, and appendicular diverticulitis. All carcinoid tumors were located in the distal appendix. Six of the 11 carcinoid tumors were defined by histopathology as involving tubular cells, and the other 5 as involving enterochromaffin cells. Six patients had muscularis propria invasion, 2 patients had submucosa invasion, 2 patients had mesoappendix invasion, and 1 patient had serosal invasion. All patients with tumors remained disease free during the follow-up (range, 127 months). We conclude that when the ratio of unusual pathologic findings for appendectomy specimens is considered, it is evident that all surgical specimens should be subjected to careful histologic examination. C1 [Emre, Arif; Kanlioz, Murat] Malatya State Hosp, Dept Surg, TR-44300 Malatya, Turkey. [Akbulut, Sami; Yilmaz, Mehmet] Inonu Univ, Dept Surg, Fac Med, TR-44280 Malatya, Turkey. [Bozdag, Zehra; Sahin, Nurhan] Malatya State Hosp, Dept Pathol, TR-44300 Malatya, Turkey. [Emre, Rabia] Malatya Publ Hlth Ctr, TR-44300 Malatya, Turkey.